PENERAPAN TEKNIK PEMBELAJARAN SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IA SD NEGERI 15 PEKANBARU - Rina '; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : One of the study aim accomplishment achievement height learns student. but evaluation result during teach at my class is country elementary school 15 pekanbaru, show in low category averagely class as big as 64.17. This watchfulness is done at his class country elementary school 15 pekanbaru school year 2014/2015. This watchfulness design class action watchfulness (ptk). subjek this watchfulness his class student is semester 2 school year 2014/2015 at country elementary school 15 pekanbaru with total 30 person. Conclusion from this watchfulness found result enhanced learns in student at his class is country elementary school 15 pekanbaru uses technique scramble. Mean study technique scramble can increase result learn his class student social science is country elementary school 15 pekanbaru. in general beginning data result before is carried out technique use scramble, student gets kerage value as big as 64.17 with category enough. My cycle repetition is class average as big as 75.17 with good category and in cycle ii be 80.83 with good category. From watchfulness result is known cycle teacher activity II meeting 1 got percentage ketercapaian as big as 79% with good category and in meeting 2 got ketercapaian as big as 88% with category very well. Student activity experiences enhanced from cycle ii meeting 1 got percentage ketercapaian as big as 92% with category very well and in meeting 2 got ketercapaian as big as 96% with category very well.Kata Kunci: study technique scramble, learns achievement